The weight of the past : living with history in Mahajanga, Madagascar. - Lambek, Michael (Contemporary Anthropology of Religion, 2002)
InThe Weight of the Past, Michael Lambek explores the complex ways that history shapes, constrains, and enables daily life. Focusing on ritual performances of spirit mediumship in a multifaceted religious landscape, Lambek's analysis reveals the multiple ways that Sakalava "bear" history. In Mahajanga, Madagascar, to bear history is at once a weighty obligation, a creative re-birthing, a scrupulous cultivation, and an exuberant performance of the past.This book describes the division of labor, creative production, and ethical practice entailed in imagining, embodying, and serving the past. It is at once a vivid ethnography of Sakalava life and a significant intervention in anthropological debates on culture and history, structure and practice, advocating a theoretical approach informed by Aristotelian categories of understanding -- Présentation de l'éditeur.